Author Correction: Tuneable poration: host defense peptides as sequence probes for antimicrobial mechanisms. Issue 1 (December 2018) - Pfeil, Marc-Philipp; Pyne, Alice; Losasso, Valeria; Ravi, Jascindra; Lamarre, Baptiste; Faruqui, Nilofar; Alkassem, Hasan; Hammond, Katharine; Judge, Peter; Winn, Martyn; Martyna, Glenn; Crain, Jason; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.